Grass Flora of Sathyamangalam Tiger Reserve, Eastern Ghats, India - Prakash, L.; Balasubramanian, P. (Indian Forester, 2021)
A systematic survey was carried out during November 2013 to October 2019 to document the grass flora occurring in Sathyamangalam Tiger Reserve, Eastern Ghats in India. A total of 175 species belonging to 73 genera and 8 subfamilies were recorded. Panicoideae is the most dominant subfamily with 112 species followed by Chloridoideae (41 species). Among the 71 genera recorded, Eragrostis is the dominant genus (15 species) followed by Panicum (10 species) and Digitaria (8 species). Sathyamangalam Tiger Reserve harbours 37.55% of Tamil Nadu state’s grass flora.